2007
DOI: 10.1680/coma.2007.160.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Making reinforced concrete immune from chloride corrosion

Abstract: Chloride-induced corrosion is a major factor affecting the durability of reinforced-concrete structures. However, a high tolerance to chloride contamination has often been achieved under laboratory conditions. A significant factor affecting the chloride threshold level for corrosion initiation in concrete is the presence of defects, such as air voids, in the cement paste at the steel–concrete interface. To explain this observation it is noted that corrosion initiation and propagation involve the local producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
4
24
0
Order By: Relevance
“…As a result galvanic protection is not generally achieved by sustaining an adequate level of steel polarisation, as is the case for other electrochemical treatments [9,11].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result galvanic protection is not generally achieved by sustaining an adequate level of steel polarisation, as is the case for other electrochemical treatments [9,11].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The new International standard for CP of steel in concrete [17] has taken this into account and performance assessment of galvanic CP is preferably focused on corrosion risk assessment. In practice this is based on monitoring of changes in the condition of the reinforcement that arise as the result of the protective effects afforded by galvanic CP [11]. Examples include corrosion potential as a function of time and/or distance from an anode or edge of the repaired area and/or corrosion rate [5,22].…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The effects of pit re-alkalisation, chloride extraction from pits and polarisation have been compared by others and on balance pit re-alkalisation and pH maintenance appear to be the dominant protective effects at typical cathodic protection current densities [17]. Indeed brief high current treatments have been shown to raise the chloride threshold level for corrosion initiation to values substantially greater than 2% chloride by weight of cement [5]. It is postulated that this is due to the generation of hydroxide at the steel.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…This is supported by the Pitting Potential/Re-passivation Potential hypothesis [1]. By contrast, it has been suggested that modifying the surface of the steel by raising the pH is the dominant protective effect, with reports that typical Impressed Current Cathodic Protection current densities are enough to halt corrosion when applied for long periods [2,3], or delay its onset in aggressive environments once the protective current has been removed [4,5]. These observations support the basis of the Pit Re-alkalisation/pH Maintenance hypothesis [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the results of a study in which a brief period of electrochemical treatment that would have generated hydroxide ions at the steel caused a substantial increase in the tolerance to chloride contamination [8]. The observation that electrochemically treated structures are more tolerant to chloride contamination is countered by an observation that in very heavily chloride contaminated concrete; corrosion may start again.…”
Section: Introductionmentioning
confidence: 99%